Liquid metal foam composite ink for 3D (three-dimensional) structure printing as well as preparation method and application of liquid metal foam composite ink

By adding inorganic filler to liquid metal and mixing mechanically, and then preparing liquid metal foam composite ink through vacuum processing, the blockage and structural instability caused by high filler content in 3D stereoscopic structure printing is solved, and high-precision and stable 3D stereoscopic structure printing is achieved.

CN119566326AActive Publication Date: 2025-03-07SICHUAN UNIV
View PDF 26 Cites 0 Cited by

Patent Information

Application Number
CN202510132312.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-03-07
Estimated Expiration
2045-02-06

AI Technical Summary

Technical Problem

The existing liquid metal inks have problems with high filler content in 3D stereoscopic structure printing, resulting in printing blockage, structural instability and corrosion, and lack of inks with low filler content, high injectability and high strength.

Method used

The liquid metal composite material is formed by adding inorganic fillers to the liquid metal and mixing mechanically, and then preparing the liquid metal foam composite ink through vacuum processing, programmable and adjusting the porosity and strength.

Benefits of technology

Liquid metal inks with low filler content, high injectability and high strength are realized, which can print 3D three-dimensional structures with high precision, avoid structural instability and corrosion problems, and simplify the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119566326A_ABST
    Figure CN119566326A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of liquid metal functional composite materials, in particular to liquid metal foam composite ink for 3D structure printing and a preparation method and application thereof.The method comprises the following steps that (1) a proper amount of liquid metal is taken to be mixed with inorganic filler through mechanical force, and a liquid metal composite material is obtained; and (2) the liquid metal composite material obtained in the step (1) is subjected to vacuum treatment, and the liquid metal foam composite ink is obtained.According to the preparation method, addition of additives such as water, an expansion substance, a foaming agent and a framework material is not needed, complex reaction processes and equipment needed by additional auxiliary forming technologies including freezing assistance, light curing, sintering and pouring are not needed, and the preparation process is simple. The novel liquid metal foam composite ink which is low in filler content, high in injectability and high in strength can be simply, rapidly and massively prepared, a high-precision and uniform 3D structure can be printed, and the novel liquid metal foam composite ink can be applied to the fields of biological medicine, aerospace, electronics, thermal interfaces and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of liquid metal functional composite materials, and in particular to a liquid metal foam composite ink for 3D structure printing, and a preparation method and application thereof. Background Art

[0002] Liquid metal (LM) has demonstrated its potential for 3D printing in many applications due to its high thermal conductivity, high electrical conductivity and flexibility. However, liquid metal is currently mainly used for 2D flat pattern printing. Compared with flat patterns, 3D printing can create complex geometric shapes, meet customized needs, and optimize material use. Its importance in the fields of medicine, aerospace, electronics and construction is becoming increasingly prominent. However, the successful printing of 3D structures requires that the ink used has appropriate rheological properties. Therefore, the ink needs to be processed and modified and rheologically regulated.

[0003] At present, the viscosity and mechanical properties of ink can be increased by adding fillers. For example, patent document CN116555654A discloses a liquid metal composite material with high printing accuracy and smoothness, which can be used for a new generation of flexible electronic 3D printing materials. Among them, continuously increasing the filler content can further increase the ink strength, but it will cause printing blockage and interruption. Another way is to prepare liquid metal foam by adding water, foaming agent, expansion material and template method, and use the effect of the oxide layer on the surface of the bubble to reduce the density of the material and improve its mechanical strength. For example, patent document CN115341117B discloses a liquid metal foam, a liquid metal foam composite material and a preparation method thereof, in which a porous structure is generated inside the liquid metal by the hydrogen generated by the reaction of liquid metal oxide and water.

[0004] However, these additional additives can cause problems such as structural instability, corrosion, and residue. For example, water-assisted self-foaming will continue after printing, resulting in changes in the size of the printed structure and structural instability, and will harden over a long period of time, limiting its flexibility. The foaming agent will be easily corroded by the liquid metal to form intermetallic compounds, affecting the performance of the liquid metal foam. Therefore, there is an urgent need to develop new liquid metal inks with low filler content, high injectability, and high strength to meet the printing needs of 3D structures. Summary of the invention

[0005] In response to the problems existing in the application of liquid metal, the present invention provides a method for preparing liquid metal foam that can print a 3D stereoscopic structure. Through ink formulation and vacuum adjustment, a three-dimensional printed structure with programmable porosity and adjustable strength can be created.

[0006] In the present invention, the liquid metal composite material refers to a liquid metal composite material obtained by adding inorganic fillers into liquid metal.

[0007] In the present invention, the liquid metal foam composite ink refers to the liquid metal foam composite ink obtained by vacuum processing the liquid metal composite material.

[0008] The liquid metal composite material and liquid metal foam composite ink of the present invention do not require the use of templates or other materials (such as water, expanded particles, foaming agents, template agents, organic hollow skeleton materials, etc.) during the preparation process, and the preparation process, equipment and operation are simple. The present invention manufactures liquid metal foam composite ink by vacuum processing, specifically, by using microbubbles generated during the preparation of liquid metal and inorganic filler as nucleating agents, and by ink formulation and vacuum control, a porous structure with adjustable porosity is generated inside the liquid metal composite material.

[0009] The present invention is achieved through the following technical solutions

[0010] A method for preparing liquid metal foam composite ink for 3D structure printing, characterized by comprising the following steps:

[0011] (1) An inorganic filler having a volume fraction of 1.25 vol% to 15 vol% is mixed with a liquid metal by mechanical force to obtain a liquid metal composite material, wherein the liquid metal is one of metal gallium, gallium-indium alloy, gallium-indium-tin alloy, or a mixture of the above liquid metals, and the inorganic filler is at least one of zinc oxide, tungsten oxide, gallium oxide, or a graded mixture thereof;

[0012] (2) vacuum treating the liquid metal composite material obtained in step (1) to obtain a liquid metal foam composite ink; the preparation process of the liquid metal foam composite ink does not include the use of water, expansion particles, foaming agent, template agent, and organic hollow skeleton material.

[0013] Wherein, the particle size of the inorganic filler in step (1) is 10 nanometers to 20 micrometers;

[0014] Furthermore, the mechanical force in step (1) is provided by ball milling, grinding or sand milling.

[0015] Furthermore, the grinding time in step (1) is 10-60 min and the rotation speed is 10-130 rpm, the purpose of which is to evenly mix the liquid metal and the filler into a paste.

[0016] Furthermore, the vacuum treatment method in step (2) is at least one of a vacuum pump, a vacuum box, a vacuum mixer, and a vacuum freeze dryer.

[0017] Furthermore, in step (2), the vacuum degree is 10-100 kPa and the time is 10-300 s.

[0018] On the other hand, the present invention provides a liquid metal foam composite ink for 3D structure printing, wherein the liquid metal foam composite ink is prepared by the aforementioned preparation method, and the liquid metal foam ink does not include water, expanding particles, foaming agent, template agent, and organic hollow skeleton material.

[0019] Furthermore, when the liquid metal foam composite ink is used for 3D printing, no additional auxiliary molding technology is required. The additional auxiliary molding technology includes freezing assistance, light curing, sintering, and casting.

[0020] Furthermore, the porosity and strength of the liquid metal foam composite ink are controlled according to the ink formulation and vacuum regulation, presenting a porous structure with multiple bubbles inside.

[0021] On the other hand, the present invention provides an application of liquid metal foam composite ink in the fields of biomedicine, aerospace, electronics and thermal interface.

[0022] The present invention also provides the application of the liquid metal foam composite ink in the fields of biomedicine, aerospace, electronics and thermal interface.

[0023] The principle of the present invention is as follows: (1) in step (1), mechanical mixing can make the liquid metal and the inorganic filler form lattice penetration and coordination, so that the liquid metal changes from a Newtonian fluid to a non-flowing fluid state of a paste, and finally obtains a liquid metal composite material; the porosity and strength of the liquid metal foam composite ink obtained in step (2) can be controlled according to the ink formula and vacuum regulation, showing a porous structure with multiple bubbles inside, the reason is that the microbubbles generated during the mixing process can serve as the nucleation points of the bubbles in the liquid metal composite material. Under the condition of vacuum, these microbubbles provide a low-pressure environment in the local area, prompting more gas to precipitate from the liquid metal or filler to form new bubbles, thereby preparing a liquid metal foam composite material. Compared with the use of additives such as water, expansion particles, foaming agent, template agent, organic hollow skeleton material additive, this method can use the mechanical chemical action in the preparation process of the liquid metal composite ink to introduce air, thereby generating microbubbles, which are used as vacuum foaming nucleating agents to prepare liquid metal foam composite ink. In the structure of bubbles in liquid metal foam composite ink, the surface gallium oxide provides additional strength and support for the overall ink, laying the foundation for the printing of 3D structures, so that when liquid metal foam composite ink is used for 3D printing, there is no need for additional auxiliary molding technologies including freezing assistance, photocuring, sintering, and pouring.

[0024] The beneficial effects of the present invention include: providing a liquid metal foam composite ink and a preparation method thereof, wherein the preparation method does not require the addition of additives such as water, expanders, foaming agents, skeleton materials, etc., does not require the complicated reaction process and equipment required for additional auxiliary molding technologies such as freezing assistance, photocuring, sintering, and pouring, and can simply and quickly prepare a large amount of liquid metal foam composite ink. A new type of liquid metal ink with low filler content, high injectability and high strength is obtained, and the high-strength ink obtained by rheological control can print high-precision and uniform 3D stereoscopic structures. It can be used in the fields of biomedicine, aerospace, electronics, thermal interfaces, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:

[0026] Figure 1 The following is a flow chart of the preparation of liquid metal foam composite ink. Liquid metal is added to inorganic fillers to form a liquid metal composite material, which is further vacuum processed to prepare the liquid metal foam composite ink;

[0027] Figure 2 The appearance and volume change images of the liquid metal composite materials with different filler volume fractions shown in Comparative Example 1 and Example 2 and the liquid metal foam composite ink after vacuum processing;

[0028] Figure 3 The SEM images of the liquid metal foam composite ink with different filler volume fractions in Example 2;

[0029] Figure 4 The SEM images of the liquid metal foam composite ink obtained at different vacuum times in Example 3;

[0030] Figure 5 is the viscosity test value of the liquid metal foam composite ink with different filler volume fractions in Example 2;

[0031] Figure 6 It is the viscosity test comparison value of the liquid metal composite material with different filler volume fractions shown in Comparative Example 1 and Example 2 and the liquid metal foam composite ink after vacuum processing;

[0032] Figure 7 are the storage modulus and loss modulus test values ​​of the liquid metal foam composite ink with different filler volume fractions in Example 2;

[0033] Figure 8 It is the viscosity test comparison value of the liquid metal composite material with different filler volume fractions shown in Comparative Example 1 and Example 2 and the liquid metal foam composite ink after vacuum processing;

[0034] Fig. 9 The printed single-line structure of Comparative Example 2 and Example 2 and the changes after being placed for one day;

[0035] Fig.10 Printing 3D structure images for liquid metal foam. DETAILED DESCRIPTION

[0036] In order to make the objectives, technical solutions and advantages of the present invention more clear and explicit, the implementation details of the present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0037] It should be noted that in the embodiments of the present invention, all expressions such as "first" and "second" are used only to distinguish two entities or parameters with the same name but different. Therefore, the use of "first" and "second" is only for the convenience of expression and should not be regarded as any limitation to the embodiments of the present invention, and will not be explained one by one in the subsequent embodiments.

[0038] It should be understood that the exemplary embodiments described herein are merely illustrative examples of the present invention. Although several embodiments are described in detail herein, various modifications and changes are entirely feasible for those skilled in the art without substantially departing from the subject matter of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.

[0039] Comparative Example 1

[0040] 1.818 g of 20 nm tungsten oxide and 127.19 g of gallium indium tin liquid metal were placed in an agate automated mortar and ground in an air environment for 20 min to obtain a paste-like LM-WO3 (1.25 vol%) composite material.

[0041] 3.635 g of 20 nm tungsten oxide and 125.38 g of gallium indium tin liquid metal were placed in an agate automated mortar and ground in an air environment for 20 min to obtain a paste-like LM-WO3 (2.5 vol%) composite material.

[0042] 7.27 g of 20 nm tungsten oxide and 122.36 g of gallium indium tin liquid metal were placed in an agate automated mortar and ground in an air environment for 20 min to obtain a paste-like LM-WO3 (5 vol%) composite material.

[0043] 10.905 g of 20 nm tungsten oxide and 119.14 g of gallium indium tin liquid metal were placed in an agate automated mortar and ground in an air environment for 20 min to obtain a paste-like LM-WO3 (7.5 vol%) composite material.

[0044] 14.54 g of 20 nm tungsten oxide and 115.92 g of gallium indium tin liquid metal were placed in an agate automated mortar and ground in an air environment for 20 min to obtain a paste-like LM-WO3 (10 vol%) composite material.

[0045] 18.175 g of 20 nm tungsten oxide and 112.7 g of gallium indium tin liquid metal were placed in an agate automated mortar and ground in an air environment for 20 min to obtain a paste-like LM-WO3 (10 vol%) composite material.

[0046] They were further subjected to rheological tests.

[0047] Comparative Example 2

[0048] 7.27 g of 20 nm tungsten oxide and 122.36 g of gallium indium tin liquid metal were placed in an agate automated mortar and ground for 20 min in an air environment to obtain a paste-like LM-WO3 (5 vol%) composite material. Subsequently, 6.48 g of water was added and grinding continued for 5 min to obtain a H20-LM-WO3 (5 vol%) foam composite material. It was loaded into a 10 ml syringe and printed using a 0.7 mm nozzle through the program set by the direct writing 3D printer.

[0049] The accuracy of the printed ink is 0.7 mm. After one day, the accuracy drops to 1 mm, and the surface of the printed ink becomes uneven.

[0050] Example 1

[0051] 1.4 g zinc oxide and 127.19 g gallium indium tin liquid metal were placed in an agate automated mortar and ground in air for 40 min to obtain a paste-like liquid metal composite material. It was then placed in a vacuum box and evacuated at 10 kPa for 300 s to obtain liquid metal-zinc oxide foam composite ink.

[0052] Example 2

[0053] The six liquid metal composite materials in Comparative Example 1 were placed in a vacuum box and vacuumed for 60 seconds at 100 kPa to obtain porous liquid metal-tungsten oxide foam composite ink. The composite ink was loaded into a 10 ml syringe and printed using a 0.7 mm nozzle through a program set by a direct writing 3D printer.

[0054] The accuracy of the printed ink is about 0.7 mm. After one day of placement, the accuracy remains unchanged at 0.7 mm, and the surface of the printed ink is smooth.

[0055] Scanning electron microscope images were taken of them, and their viscosity and modulus values ​​were measured using a rotational rheometer. It was found that as the filler content of the liquid metal-tungsten oxide foam composite ink increased, the total volume of bubbles first increased and then decreased. The viscosity and modulus of the liquid metal foam composite ink were greatly improved compared to the liquid metal composite material.

[0056] Example 3

[0057] The LM-WO3 (5 vol%) composite material obtained in Example 2 was divided into five equal parts and placed in a vacuum box. The vacuum was drawn at 100 kPa for 0 s, 10 s, 60 s, 90 s, and 120 s to obtain liquid metal-tungsten oxide foam composite inks with different vacuum times.

[0058] Scanning electron microscope images were further taken of them, and it was observed that under the vacuum condition of 100 kp, the cavitation volume first increased and then decreased with the increase of vacuum time.

[0059] Figure 1 The preparation flow chart of liquid metal foam composite ink is shown. Pure liquid metal presents a low-viscosity fluid state, and due to the high surface tension, it spontaneously shrinks to form a spherical droplet; after adding inorganic fillers, a uniform paste-like liquid metal composite material is formed; further vacuum processing forms a volume-expanded porous liquid metal foam composite ink.

[0060] Figure 2 The appearance and volume change images of the liquid metal composite materials with different filler volume fractions and the liquid metal foam composite ink after vacuum processing shown in Comparative Example 1 and Example 2 are shown. It can be seen from the figure that the volume of the liquid metal composite material increases significantly after vacuum processing, and as the filler volume fraction increases, the total volume of the bubbles increases first and then decreases. Among them, the total volume of the liquid metal foam composite ink can reach up to 2.5 times the total volume of the liquid metal composite material.

[0061] Figure 3 SEM images of liquid metal foam composite inks with different filler volume fractions in Example 2 are shown. As can be seen from the figure, increasing the filler content leads to an increase in the number of bubbles. The filler particles can act as nucleation sites to help the gas precipitate from the liquid metal matrix to form bubbles. Higher filler content provides more nucleation sites, thereby increasing the total number of bubbles.

[0062] The increase in filler content also leads to a decrease in bubble size. This is because more filler particles mean that the bubble nucleation sites are more dispersed, and the available volume near each nucleation site is smaller, thus limiting the growth space of individual bubbles.

[0063] Figure 4The SEM images of the liquid metal foam composite ink obtained at different vacuum times in Example 3 are shown. It can be seen from the figure that under the vacuum condition of 100kp, as the vacuum time increases, the cavitation volume first increases and then decreases. In a short period of time, the original microbubbles are nucleation points that gradually expand under low pressure, and the total volume of the foam pores increases. However, when the vacuum time is too long, exceeding 60s, the continuous low pressure causes the pores to merge, and collapse into a layered structure after the vacuum is withdrawn, and the total volume of the foam pores decreases.

[0064] Figure 5 The viscosity test values ​​of the liquid metal foam composite ink with different filler volume fractions in Example 2 are shown. As can be seen from the figure, the viscosity value of the liquid metal foam composite ink gradually increases with the increase of the filler volume fraction.

[0065] Figure 6 The viscosity test comparison values ​​of the liquid metal composite materials with different filler volume fractions shown in Comparative Example 1 and Example 2 and the liquid metal foam composite ink after vacuum processing are shown. From the comparison values, it can be seen that the viscosity of the liquid metal foam is significantly improved compared with the liquid metal ink before vacuum, and the micropores play a key role in this. The larger the total volume of bubbles, the more obvious the effect on the rheological behavior of the liquid metal. The rheological behavior of the liquid metal filler at a volume fraction of 5% is close to the viscosity value of the liquid metal ink filler volume fraction of 10% before vacuum. The filler volume fraction required to achieve high viscosity is significantly reduced.

[0066] Figure 7 The storage modulus and loss modulus test values ​​of the liquid metal foam composite ink with different filler volume fractions in Example 2 are shown. As can be seen from the figure, the storage modulus and loss modulus values ​​of the liquid metal foam composite ink gradually increase with the increase of the volume fraction of the filler.

[0067] Figure 8 The storage modulus and loss modulus test comparison values ​​of the liquid metal composite materials with different filler volume fractions shown in Comparative Example 1 and Example 2 and the liquid metal foam composite ink after vacuum processing are shown. From the comparison values, it can be seen that the modulus of the liquid metal foam is significantly improved compared with the liquid metal ink before vacuum.

[0068] Fig. 9The printed single-line structure of Comparative Example 2 and Example 2 and the changes after one day of placement are shown. The upper figure shows the images of the H20-LM-WO3 (5 vol%) foam composite material with water as an additive before and after placement. The precision of the printed ink is 0.7 mm. After one day of placement, the precision drops to 1 mm, and the surface of the printed ink is uneven and uneven. The lower figure shows the images of the vacuum-foamed LM-WO3 (5 vol%) foam composite material of the present invention before and after placement. The precision of the printed ink is about 0.7 mm. After one day of placement, the precision remains unchanged at 0.7 mm, and the surface of the printed ink is smooth.

[0069] Fig.10 The image of the 3D structure printed by liquid metal foam is shown, and the printing accuracy is 180 μm. The high strength, high viscosity and high modulus of the liquid metal foam can meet the purpose of self-supporting three-dimensional molding without relying on any auxiliary molding means (such as freezing assistance, light curing, sintering, pouring, etc.) during the printing process, thereby constructing a printed product with a 3D structure. By further designing the printing path, it can be applied to the manufacture of complex structures in the fields of biomedicine, aerospace, electronics and thermal interfaces.

[0070] The physical and chemical properties of liquid metal foam composite inks include:

[0071] Rheology of inks: The rheological properties of the inks were evaluated using a MCR302 rheometer (Anton Paar, Austria).

[0072] The measurements were performed in a plate-plate geometry with an 8 mm diameter and a 1 mm gap, maintaining a constant temperature of 25 °C.

[0073] Microstructure characterization: The liquid metal foam composite ink was frozen with liquid nitrogen and cut into pieces.

[0074] The cross-sectional morphology of the ink was characterized by Hitachi S-4800.

[0075] In summary, if you want to obtain a liquid metal foam composite material with the highest porosity, you can choose a moderate filler volume fraction (about 5%), a small particle size (20 nm), and a moderate vacuum time (60 s). Higher porosity can increase the content of spontaneously produced gallium oxide layer on the bubble surface, and use the effect of the oxide layer on the bubble surface to reduce the density of the material and improve its mechanical strength. In the preparation process of the present invention, no template or other materials (such as water, expanded particles, foaming agents, templates, organic hollow skeleton materials, etc.) are required, and the preparation process, equipment and operation are simple. It avoids the adverse effects of additives on ink printing, such as water-assisted self-foaming will continue after printing, resulting in changes in the size of the printed structure and structural instability, and long-term hardening will limit its flexibility.

[0076] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing liquid metal foam composite ink for 3D structure printing, characterized in that: It consists of the following steps: (1) An inorganic filler having a volume fraction of 1.25 vol% to 15 vol% is mixed with a liquid metal by mechanical force to obtain a liquid metal composite material, wherein the liquid metal is one or a mixture of metal gallium, a gallium-indium alloy, a gallium-indium-tin alloy, and the inorganic filler is at least one of zinc oxide, tungsten oxide, and gallium oxide, or a graded mixture thereof; (2) vacuum treating the liquid metal composite material obtained in step (1) to obtain a liquid metal foam composite ink; the preparation process of the liquid metal foam composite ink does not include the use of water, expansion particles, foaming agent, template agent, and organic hollow skeleton material.

2. The method for preparing liquid metal foam composite ink for 3D structure printing according to claim 1, characterized in that: The particle size of the inorganic filler in step (1) is 10 nanometers to 20 micrometers.

3. The method for preparing liquid metal foam composite ink for 3D structure printing according to claim 2, characterized in that: The mechanical force in step (1) is provided by ball milling, grinding or sand milling.

4. The method for preparing liquid metal foam composite ink for 3D structure printing according to claim 3, characterized in that: The grinding time in step (1) is 10-60 min and the rotation speed is 10-130 rpm, the purpose of which is to evenly mix the liquid metal and the filler into a paste.

5. The method for preparing liquid metal foam composite ink for 3D structure printing according to claim 4, characterized in that: The vacuum treatment method in step (2) is at least one of a vacuum pump, a vacuum box, a vacuum mixer, and a vacuum freeze dryer.

6. The method for preparing liquid metal foam composite ink for 3D structure printing according to claim 5, characterized in that: In step (2), the vacuum degree is 10-100 kPa and the time is 10-300 s.

7. A liquid metal foam composite ink for 3D structure printing, characterized in that: The liquid metal foam composite ink is prepared by the preparation method according to any one of claims 1 to 6, and the liquid metal foam composite ink does not include water, expansion particles, foaming agent, template agent, and organic hollow skeleton material.

8. The liquid metal foam composite ink according to claim 7, characterized in that: When the liquid metal foam composite ink is used for 3D printing, no additional auxiliary molding technology is required. The additional auxiliary molding technology includes freezing assistance, light curing, sintering, and casting.

9. The liquid metal foam composite ink according to claim 8, characterized in that: The porosity and strength of the liquid metal foam composite ink are controlled according to the ink formula and vacuum regulation, presenting a porous structure with multiple bubbles inside.

10. Application of the liquid metal foam composite ink according to any one of claims 8 to 9 in the fields of biomedicine, aerospace, electronics and thermal interface.

Citation Information

Patent Citations

  • A liquid metal foam, a liquid metal foam composite material and its preparation method

    CN115341117B

  • Foam ink composition and 3D printed hierarchical porous structure

    CN107709478A

  • Preparation method of light curing molding potassium-sodium niobate leadless piezoelectric ceramics

    CN109650887A

  • Pretreatment method and device for circuit board heat dissipation ink

    CN110917982A

  • Preparation method and application of high-thermal-conductivity foam composite phase change material

    CN113308227A